Efeito do revestimento de quitosana sobre a qualidade e fisiologia pós-colheita do pedúnculo de Anacardium occidentale L. - Gomes, Camila Ribeiro dos Santos (2021)
Cashew has a short postharvest shelf life and, therefore, this study aimed to evaluate the effect of chitosan coating on its quality and postharvest physiology. BRS 189 cashew stalks were coated with a 2% (w/v) chitosan solution and stored at 5 ºC and 90% RH for 10 days, while the control consisted of uncoated fruits kept in the same condition. Every two days, the peduncles were analyzed for mass loss; pH; soluble solids; titratable acidity; SS/AT ratio; firmness, cell wall hydrolytic enzyme activity and antioxidant metabolism. The coated peduncles showed increased firmness after 10 days of storage, which can be elucidated by the low activity of PME. This study contributed to clarifying the physiological and biochemical influence of edible coatings of chitosan on cashew and with it the reduction of natural waste and consequently the reduction of natural resources applied in its production due to better use in cashew crops